OSTEOMYELITIS: A COMPREHENSIVE REVIEW OF PATHOGENESIS, DIAGNOSIS, AND MANAGEMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Osteomyelitis is a severe bone tissue infection commonly caused by bacterial pathogens, with Staphylococcus aureus being the predominant organism. This study explores the epidemiology, pathogenesis, clinical presentation, diagnostic modalities, and treatment strategies for osteomyelitis. A literature review was conducted to analyze current trends in diagnosis and management. The findings emphasize the importance of early detection through imaging and microbiological assessments and the role of antimicrobial therapy and surgical intervention. Future research should focus on novel treatment modalities and preventive strategies.